Private International Law Methods for the Protection of the Employee - Marino, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The work tackles the main methods of private international law in order to verify their use and effectiveness in the context of the protection of the worker as a weak party in the EU civil ju-dicial cooperation. After recalling the main developments of the sources, the contribution examines the notion of worker in EU Law. Then, it analyses the typical methods of the localization and the principle of proximity, of the alternativity and succession of the grounds of jurisdiction and of the connecting factors, of the limits to the party autonomy, as suitable tools to guarantee protection to the worker. A specific paragraph is reserved to the circulation of judgments in the European judicial area.